High Speed C-V Converter - Sakalauskas, S.; Vaitonis, Z.; Puras, R.; Bulbenkiene, V. (Elektronika ir Elektrotechnika, 2008)
Theoretical analysis and experimental investigation of the method to measure capacitance and structure’s capacitance-voltage characteristics by means of linearly varying voltage showed a linear dependence between the output voltage and capacitance (when transient process is over). Whereas the duration of transient process is determined mainly by the value of measured capacitance multiplied by resistance, the transient duration may be reduced by lowering resistor’s value, though it decreases signal to noise ratio. We choose another solution – the compensation of electric capacitance, which very effectively reduces (by a factor of several tens) the transient duration and does not affect the relationship measured capacitance – output voltage. It increases the operation speed of capacitance-voltage converter. Ill. 4, bibl. 7 (in English; summaries in English, Russian and Lithuanian).